Research on River-lake Demarcation Technology Fusing Radar Point Cloud andOrthophoto - XIA Zuwei; RONG Lihui (Renmin Zhujiang)
In the demarcation of rivers, lakes and water conservancy projects, whenthe airborne lidar point cloud data is used alone to automatically filter andclassify, low vegetation points are easily misclassified and misjudged as groundpoints,affected by the dense distribution of vegetation in the measured area, thusresulting in the failture of accurately extracting interest elevation featurelines. Combining the characteristics of rich spectral information and high groundresolution of orthophotos, this paper proposes a method of accurate extraction ofmanagement and protection range lines fusing point cloud and orthophotos, andapplies it to the Nanwan Reservoir project. The results show that the method isfeasible for river chiefssystem management and protection range line extraction,which can greatly shorten the production cycle and save production costs, so it isof good practical promotion value.